TEACHER’S BELIEFS AND PRACTICE TOWARD THE TEACHING READING STRATEGIES TO FOSTER STUDENTS’ CRITICAL THINKING - Rahmaniah Oktaviah; Johannes Ananto Prayogo; M Misbahul Amri (Jurnal Pendidikan Humaniora, 2021)
Abstract: This is a case study designed to investigate the Advanced Reading teacher’s beliefs in teaching reading and their practice, especially by involving critical thinking. It is obtained that the teacher believes in several strategies in teaching reading, which are case study, group discussion, and presentation of the text’s summary. While for the teaching practice the teacher implements several strategies which are group and classroom discussion, presentation and questioning, summarizing, and also storytelling. Some of the strategies are congruent with the teacher’s beliefs and some others are not in line with the teacher’s beliefs.Keywords: teacher’s belief, strategies, critical thinking Abstrak: Penelitian ini dilaksanakan melalui metode case study untuk mengetahui konsep guru dalam strategi pengajaran Reading serta tindakan praktikal yang dilakukan di kelas, terutama dalam mengintegrasikan pola berfikir kritis dalam kegiatan Reading. Hasil penelitian ini menunjukkan bahwa guru memiliki pandangan terhadap beberapa strategi mengaajr Reading yaitu studi kasus, diskusi dalam grup, dan presentasi dari hasil menyimpulkan bacaan. Sedangkan dalam kegiatan mengajar, guru menerapkan diskusi grup dan kelas, presentasi dan tanya jawab, membuat kesimpulan, dan juga menceritakan kembali. Beberapa strategi yang diterapkan di kelas sesuai dengan konsep yang dimiliki guru, dan beberapa strategi tidak sesuai dengan konsep yang dimiliki.Kata Kunci: keyakinan guru, strategi, berpikir kritis